Penggunaan Unmanned Aerial Vehicle untuk Pemetaan Lahan Wisata Desa Sindang Pakuwon Parakan Muncang - Toni Kusnandar (Masoem University, 2020)
At present mapping using Unmanned Aerial Vehicle (UAV) technology is a popular alternative. The use of UAVs by the public is increasing because more and more manufacturers are marketing their products and are available in the market. Apart from the relatively affordable price, UAV features and capabilities are increasing. DroneDeploy and Agisoft have simplified the process of making maps. Monitoring software can be used starting from planning, implementation, processing, to the results of processing.The planned development of a tourist area in the area of Sindang Pakuwon Village which is a village in the Cimanggung District area of Sumedang Regency, requires a location map as a condition for submitting the construction permit. Landowners need to make a representative, economical but still quality map.Utilization of multi-rotor copter type UAVs that are more widely available and the availability of software, has a resource plan that is efficient and very fast, but is quite accurate and representative.